Diachronic Research into Translation Norms: The Case of Literary Discourse - Butkuvienė, Karolina; Petrulionė, Lolita (Vertimo studijos, 2023)
The article addresses the issue of the translation of fiction in different periods of time under the influence of various linguistic, social and cultural norms, and it aims to establish differences in the use of translation strategies employed by the translator. The paper reviews the descriptive approach in Translation Studies which argues that translation is a communicative as well as social act where the translator alone is not responsible for his/her translational behaviour; other people and institutions also contribute to the formation of common notions of translational behaviour, and these are termed norms, conventions or rules. Moreover, the research emphasizes that norms are not a stable phenomenon and may vary across different periods of time and across different cultures or communities. The research is based on the contrastive analysis of two translations of Jack London’s Martin Eden with the aim to establish differences in the use of translation strategies under the influence of translation norms.
Keywords: translation; norms; conventions; rules; descriptive approach